Edward Hart: Bricklayer, Theologian and Nonjuring Martyr - Lewis, Simon (My University, 2021)
This paper explores the neglected manuscripts and publications of Edward Hart, an early eighteenth-century Nonjuring bricklayer, whose determination to promote his cause ultimately led to his death. By discussing Hart’s support for High Church doctrines, such as the apostolic succession and non-resistance, this study challenges traditional historiographical associations between artisan theology and ‘radical’ anticlericalism, while also illuminating the fundamental role played by the Nonjuring laity in the dissemination of conservative politico-theological ideas. Moreover, by discussing Hart’s defence of Anglican ‘orthodoxy’, this paper shows that the Nonjurors operated not on the fringes but in the very centre of the early eighteenth-century politico-theological arena. Despite his fierce opposition to the perceived anticlericalism of Latitudinarians and Dissenters, Hart was not entirely subservient to Nonjuring divines. Rather, Hart openly challenged the liturgical reforms proposed by some Nonjuring clergymen, which, he believed, threatened the dwindling communion’s survival.
PUBLISHED
Keywords: Nonjurors; Anglicanism; Eighteenth-Century England; Liturgy; Toryism; British History; Ecclesiastical History; History